Meningkatkan Nilai Ekonomis melalui Pengelolaan Hasil Pertanian dan Perkebunan dengan Sistem Akuntansi Keuangan di Desa Pancakarya, Kabupaten Karawang - Triyono, Triyono; Tabah Rizki; Arina Hidayati (Jurnal Pengabdian Masyarakat - PIMAS, 2025)
The underutilization of agricultural and plantation products is the primary issue faced by the people of Pancakarya Village, Karawang Regency. This has an impact on the relatively low economic value of the products produced. This community service program is designed to enhance the community’s financial management capabilities through training in simple accounting systems. Partners for this service include farmer groups, PKK mothers, and village youth, who are located in fertile areas with abundant agricultural and plantation potential, through the Participatory Action Research (PAR) Approach, which is a program implemented through a series of workshops and practical assistance covering financial recording techniques, stock management, and pricing strategies. With 75% of participants able to create basic financial reports, the program’s outcomes show a notable improvement in partners’ comprehension of basic accounting. After training, participants’ comprehension and awareness are significantly improved by this program as well